ASSOTIATION OF THE GENETIC POLYMORPHISM E670G OF THE PCSK-9 AND THE SEVERITY OF THE CAROTID ATHEROSCLEROSIS IN PATIENTS WITH HETEROZYGOUS FAMILIAL HYPERCHOLESTEROLEMIA IN UZBEK POPULATION - R. B. Alieva; S. U. Hoshimov; Sh. S. Ahmedova; F. M. Bekmetova; A. B. Shek; R. D. Kurbanov (Евразийский Кардиологический Журнал, 2019)
Objective: to study the severity of carotid artery atherosclerosis in patients with heterozygous familial hypercholesterolemia in the Uzbek population, depending on the level of PCSK-9 and the genetic polymorphism E670G of the PCSK-9 gene.Material and methods. The study included 57 patients with chronic stable coronary artery disease (SCAD) and familial heterozygous hypercholesterolemia (HeFH, group I). The comparison group consisted of 144 patients with SCAD without HeFH divided into two subgroups: A - statin free before the research (n=63) and B (n=81) who took it as outpatients; control group consisted of 17 healthy people. The level of proprotein convertase subtilisin-kexin type 9 (PCSK-9) was measured with Human Proprotein Convertase 9/PCSK9 ELISA Kit (MULTI SCIENCE, China). The genetic typing of PCSK9 E670G (rs505151) polymorphism was performed by means of the PCR-RFLP method.Results. A comparison of the results of duplex scanning of carotid arteries in patients with HeFH showed that the carotid intima-media thickness (CIMT) on the left (1.14±0.18 mm, P<0.01) and on the right (1.15±0.16 mm, P<0.01) was higher, than in the comparison group: 1.05±0.17 mm and 1.04±0.18 mm, respectively. The studies revealed a positive correlation between the incidence of Myocardial infarction (MI) in the history in patients with HeFH and the (r=0.38, P<0.05). The CIMT also correlated with an increase in the concentration of PCSK9 (r = 0.31, P <0.05) in the blood and the carriage of the G allele of polymorphism E670G (r = 0.39, P <0.05) of the PCSK9 gene.Conclusion. Inpatientswithheterozygousfamilialhypercholesterolemia in the Uzbek population a direct correlation was established between Myocardial infarction in the history, the carotid intima-media thickness, an increase in the concentration of PCSK-9 in the blood and the carriage of the G allele of E670G polymorphism of the PCSK9 gene, that allows them to be used as prognostic markers for the risk of development of cardiovascular complications.